Predictors of severe psychological distress trajectory after nuclear disaster: evidence from the Fukushima Health Management Survey. Issue 10 (19th October 2016) - Oe, Misari; Maeda, Masaharu; Nagai, Masato; Yasumura, Seiji; Yabe, Hirooki; Suzuki, Yuriko; Harigane, Mayumi; Ohira, Tetsuya; Abe, Masafumi
Abstract : Objectives: The Fukushima Daiichi Nuclear Power Plant accident, which occurred after the Great East Japan Earthquake and Tsunami in March 2011, may have a considerable long-term impact on the lives of area residents. The aims of this study were to determine the trajectories of psychological distress using 3-year consecutive data, and to find predictive factors of severe distress that may also prove useful for public health intervention. Methods: Data were obtained on 12 371 residents who were registered in the municipalities categorised as complete evacuation areas for 3 years after the disaster and who completed an assessment in each of the 3 years. Results: Using group-based trajectory modelling, we identified four trajectory patterns distinguished by the levels of psychological distress, which gradually improved over time in all trajectories. Subjective sleep insufficiency, problem drinking, poor social support and perception of radiation risk 3 years after the accident were associated with the severity of psychological distress, according to the multivariate analysis. Conclusions: The identified factors may be useful for community-based mental healthcare over the long term following a nuclear disaster.